Factors Affecting the Occurrence of Mental Disability in Ponorogo District, East Java (Journal of Maternal and Child Health, 2017)
Background: Children with mental disability show below average intellectual abilities and social behavior adaptability. Living with a disabled child can have profound effects on the entire family